MENGGAGAS ETIKA DAKWAH DI RUANG MEDIA SOSIAL - Mastori Mastori; Athoillah Islamy (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
This study intends to explore various values ​​of Islamic teachings that can be used as a da'wah code of ethics in the social media space. This research is qualitative research in the form of library research. The main data sources used are various scientific literature, both in the form of books (books) and scientific journals related to the discussion of ethical values ​​in preaching on social media. Meanwhile, secondary research data sources used are various scientific literature relevant to the core object of this research. This research is categorized as conceptual research with a philosophical normative approach. Meanwhile, the nature of this research approach is descriptive-analytic. However, it is not only descriptive-analytic but also prescriptive. The results of the study show that there are various values ​​of Islamic teachings that can be used as ethical values ​​of indictment in the social media space (socmed). These ethical values ​​include being sincere and true, honest, and avoiding coachman debates